Radiotherapy-Induced Cognitive Sequelae - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Long-term neurological and neuropsychological outcome in 25 irradiated children <15-years of age and 25 treated with surgery alone for low-grade astrocytoma was evaluated by two neurosurgeons and two psychologists independently at the Royal Manchester Children's Hospital, UK.